Solving the mystery: the true prevalence of gestational diabetes in indigenous women. Issue 5 (12th May 2015) - Saad, Nathalie; Wilson, Don; Donovan, Lois E.
Abstract This commentary briefly reviews what is currently known about estimating the prevalence of gestational diabetes in indigenous women. It offers insights into numerous factors likely playing a role in its observed variability. It also highlights important key concepts to consider in the overall evaluation and management of gestational diabetes in this particular population. Copyright © 2015 John Wiley & Sons, Ltd.